Cord Blood Transplantation: Can We Make it Better? - Metheny, Leland; deLima, Marcos (Frontiers in Oncology, 2013)
Umbilical cord blood is an established source of hematopoietic stem cells for transplantation. It enjoys several advantages over bone marrow or peripheral blood, including increased tolerance for Human Leukocyte Antigen mismatches, decreased incidence of graft-versus-host disease, and easy availability. Unrelated cord blood does have limitations, however, especially in the treatment of adults. In the 24 years since the first umbilical cord blood transplant was performed, significant progress has been made, but delayed hematopoietic engraftment and increased treatment related mortality remain obstacles to widespread use. Here we summarize the latest results of unrelated cord blood transplants, and review strategies under investigation to improve clinical outcomes.